Kepuasan Pelaku Usaha Perikanan Terhadap Kinerja Penyuluh Di Kabupaten Mahakam Ulu - Fitriyana fitriyana; Fredinan Yulianda; Bambang Widigdo (Universitas Mataram, 2024)
Fisheries business actors often receive little attention from the government, especially from fisheries instructors, this often results in fundamental problems such as suboptimal capture and aquaculture production results, which can result in uncertain income. The research was carried out in Mahakam Ulu Regency in 2022 starting from August to December. The aim of the research is to determine the level of satisfaction of fisheries actors with the performance of fisheries instructors, determine the processes carried out to improve the performance of fisheries instructors, and find out the obstacles faced by instructors in carrying out extension activities. The method used was purposive sampling to determine respondents to be sampled based on certain criteria. The analysis method uses a Likert scale. The results of the study showed that the average satisfaction level of fisheries actors was 2.50, which means that fisheries actors were less satisfied with the performance of fisheries instructors. The obstacles faced by fisheries instructors were in terms of location access, instructor staff, facilities and infrastructure, government policy, participation and activeness group